Activating an artisanal saltpan: tourism crowding in or waterbirds crowding out? - Ramos, Jorge (2022)
Purpose There is an increasing interest in visiting protected areas in the Algarve (Portugal). Tourists are interested in contact with nature activities. However, protected areas are quite sensitive to human pressure and are limited in their carrying capacity. The purpose of this study is to fill a literature gap concerning which features attract tourists who visit saltpans via a pedestrian tour and what sort of pressure they inflict on waterbirds' behaviour. Design/methodology/approach The tour consists of a predefined path with interpretive boards and guides who provide explanations to visitors. This study is threefold: to find out if waterbirds are disturbed by the presence of tourists, if tourists prefer to learn more about saltpans instead of finding waterbirds and if tourists have any preferred waterbird species. The methods used are direct observations with binoculars of the saltpan area and a short questionnaire. With the data collected, three hypotheses are tested. Findings The results show that the occurrence of waterbirds does not vary according to the presence or absence of tourist visits, tourists prefer visiting saltpans rather than watching waterbirds and there is some waterbird species preference. Practical implications Few people can visit the saltpan while keeping disturbance of both waterbirds and workers to a minimum. This study gives insights into sustainable ecotourism practices and how to articulate them with saltpan works. Originality/value The value of this study can be demonstrated by the interconnection between traditional salt production, waterbirds' habitat, visitors' interest and their interaction.